The Effect of Medication Adherence and Controlled HbA1c to Blood Pressure and ASCVD Risk in Hypertensive and Type 2 Diabetes Mellitus Patients: A multicenter study in Primary Health Care - C. Vera Dwi Pratiwi; Phebe Hendra; Agustina Rimanita Fortinasari; Dita Maria Virginia (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Background: Hypertension and type 2 diabetes mellitus (T2DM) are significantly increasing the risk of cardiovascular complications. The effects of medication adherence and glycemic control have been studied extensively, in part, on blood pressure or atherosclerotic cardiovascular disease (ASCVD) risk. The purpose of this study was to analyze the effect of medication adherence and controlled HbA1c levels on blood pressure and ASCVD risk among patients with hypertension and T2DM. Method: We conducted observational study with cross-sectional design to analyze the medical record data. Data were extracted from the medical records of patients diagnosed with T2DM and hypertension as comorbid at DIY primary health care (PHC). Adherence was measured quantitatively using the Medication Possession Ratio (MPR) and qualitatively using the Medication Adherence Rating Scale-5 (MARS-5). The ASCVD risk was assessed using the Framingham Risk Score. We performed chi-square and multivariate logistic analyses to analyze the relationships between variables. Results: A total of 720 respondents were recruited and participated in our study, but only 127 fulfilled the requirements. The uncontrolled blood pressure and high-risk ASCVD were 34.6% and 84.3%, respectively. The MPR was significantly higher in the controlled blood pressure group (P-value = 0.04), but not in the MARS-5 parameters (P-value 0.98). Females tended to have high-risk ASCVD (P-value 0.01). The study could not detect a significant association between adherence and controlled HbA1c to uncontrolled blood pressure and high-risk ASCVD, either in bivariate analysis or after adjusting for some variables (P-value > 0.05). Conclusion: Controlled HbA1c level and adherence were not significantly associated with uncontrolled blood pressure or high-risk ASCVD.